1999
DOI: 10.1161/01.res.85.5.428
|View full text |Cite
|
Sign up to set email alerts
|

Atrial L-Type Ca 2+ Currents and Human Atrial Fibrillation

Abstract: Chronic atrial fibrillation (AF) is characterized by decreased atrial contractility, shortened action potential duration, and decreased accommodation of action potential duration to changes in activation rate. Studies on experimental animal models of AF implicate a reduction in L-type Ca2+ current (I(Ca)) density in these changes. To evaluate the effect of AF on human I(Ca), we compared I(Ca) in atrial myocytes isolated from 42 patients in normal sinus rhythm at the time of cardiac surgery with that of 11 chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
297
0
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(354 citation statements)
references
References 34 publications
43
297
0
9
Order By: Relevance
“…The reduction in rate adaptation shown by the models is in agreement with a number of experimental studies that show little rate adaptation in MAP recordings shortly after cardioversion of chronic AF (Franz et al, 1997;Kamalvand et al, 1999;Manios et al, 2000;Osaka et al, 2000) and in isolated myocytes (Bosch et al, 1999;Van Wagoner et al, 1999;Workman et al, 2001) and tissues (Boutjdir et al, 1986) obtained from right atrial appendage tissue of patients with chronic AF. In some cases, more significant rate adaptation can be observed at the shortest CLs (Kim et al, 2002;Dobrev and Ravens, 2003).…”
Section: Atrial Fibrillation-induced Changes In Rate Dependence and Msupporting
confidence: 88%
See 1 more Smart Citation
“…The reduction in rate adaptation shown by the models is in agreement with a number of experimental studies that show little rate adaptation in MAP recordings shortly after cardioversion of chronic AF (Franz et al, 1997;Kamalvand et al, 1999;Manios et al, 2000;Osaka et al, 2000) and in isolated myocytes (Bosch et al, 1999;Van Wagoner et al, 1999;Workman et al, 2001) and tissues (Boutjdir et al, 1986) obtained from right atrial appendage tissue of patients with chronic AF. In some cases, more significant rate adaptation can be observed at the shortest CLs (Kim et al, 2002;Dobrev and Ravens, 2003).…”
Section: Atrial Fibrillation-induced Changes In Rate Dependence and Msupporting
confidence: 88%
“…In some cases, more significant rate adaptation can be observed at the shortest CLs (Kim et al, 2002;Dobrev and Ravens, 2003). Similar alterations to those given by Courtemanche et al (1999) have been observed in other experiments as well (Dobrev and Ravens, 2003), including substantial reductions in I Ca,L (Bosch et al, 1999;Van Wagoner et al, 1999;Skasa et al, 2001;Workman et al, 2001) and I to (Van Wagoner et al, 1997;Bosch et al, 1999;Brandt et al, 2000;Grammer et al, 2000;Workman et al, 2001). The reduction in I Kur proposed by Courtemanche et al (1999) has been found in some studies (Van Wagoner et al, 1997;Brandt et al, 2000) but not in others (Grammer et al, 2000;Workman et al, 2001).…”
Section: Atrial Fibrillation-induced Changes In Rate Dependence and Msupporting
confidence: 83%
“…In patients with AF, the difference between reduced 5-HT signals and catecholamine signals became more pronounced (Figs. 4 and 5), possibly related to the well-known increase in atrial myocyte size in AF (3,4). This would increase the diffusion path and dissipation of cAMP from its formation by the cell membrane-bound AC to its intracellular effectors.…”
Section: Kn-93 Reduces Ne-evoked Increases Of I Cal In Patients Withmentioning
confidence: 99%
“…Atrial contractility is reduced in isolated atrial tissues (3) obtained from patients with chronic AF, attributed to a marked decrease in L-type Ca 2+ current (I Ca,L ) (3,4). The inotropic responses to the agonist for β 1 -adrenergic receptors (β 1 ARs) and β 2 -adrenergic receptors (β 2 ARs), isoproterenol (ISO), but not the density of βARs and G proteins, are decreased in AF (3); however, whether the function of coexisting β 1 ARs and/or β 2 ARs is perturbed is unknown.…”
Section: Fig 1 Bone Cells Express Avprs Immunofluorescence Microgrmentioning
confidence: 99%
“…in density or role of the L-type calcium channel have been implicated in a variety of cardiovascular diseases 16,17 . Given this information, the objective was to test the hypothesis that chronic stress promotes cardiac dysfunction associated to L-type calcium Ca 2+ channel activity depression.…”
Section: Introductionmentioning
confidence: 99%